2016
DOI: 10.1111/ane.12700
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deterioration in adult epilepsy: clinical characteristics of “Accelerated Cognitive Ageing”

Abstract: A subgroup of patients with localization-related epilepsy exhibits cognitive decline characterized by deterioration in PIQ and FSIQ, but with preserved higher order functions (VIQ and memory). Patients typically have epilepsia tarda, comorbid pathology, relatively low educational level and older age. These are factors known to increase the vulnerability of the brain by diminishing cognitive reserve. Cognitive deterioration may develop according to a stepwise "second-hit model", affecting and accelerating the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
2
23
1
1
Order By: Relevance
“…The covariate effects, including comorbidities, are in line with those from previous publications and generally in similar ranges for dementia and AD. For example, depression and epilepsy are known to affect cognitive decline . The effect of stroke on dementia of any type is considerably larger than on AD.…”
Section: Discussionmentioning
confidence: 99%
“…The covariate effects, including comorbidities, are in line with those from previous publications and generally in similar ranges for dementia and AD. For example, depression and epilepsy are known to affect cognitive decline . The effect of stroke on dementia of any type is considerably larger than on AD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Breuer and co-workers screened 287 adult patients for cognitive deterioration compared to expected premorbid IQ (defined as ≥1 SD discrepancy between actual WAIS IQ and estimated premorbid IQ) ( Breuer et al , 2017 ). A group of 27 individuals fulfilled the criteria (mean age: 55.7; mean seizure duration: 21.8 years).…”
Section: Cognitive Function In Older Patients With Epilepsymentioning
confidence: 99%
“…More than 77% of them had associated comorbidities (including 52% cardiovascular, 14% cerebrovascular and 24% traumatic brain injury). Analyses revealed that the most prominent factors that accounted for the variance in cognitive deterioration were those that might impact on cognitive reserve: low premorbid IQ and education level, later age of seizure onset and older age ( Breuer et al , 2017 ). These findings would be consistent with a double hit model in which pre-existing low brain reserve makes the brain more vulnerable to a second hit from the development of epilepsy.…”
Section: Cognitive Function In Older Patients With Epilepsymentioning
confidence: 99%
“…So, although several studies point to BD as a risk factor for dementia, we question whether the cognitive dysfunctions present in some of these patients are not enough to affirm that there also a "bipolar dementia", just like it's done in other pathologies such as Parkinson's disease 6 and epilepsy 7 . In fact, Parkinson's disease, epilepsy and BD patients who develop cognitive dysfunction do not present the changes in the cerebrospinal fluid as are described in Alzheimer's disease, such as low concentrations of beta amyloid protein and high concentrations of total and phosphorylated tau protein 5 .…”
Section: Dear Editormentioning
confidence: 89%